Nano-imaging collagen by atomic force, near-field and nonlinear microscope - Lim, Ken Choong (2015)
As the most abundant protein in the human body, collagen has a very important role in vast numbers of bio-medical applications. The unique second order nonlinear properties of fibrillar collagen make it a very important index in nonlinear optical imaging based disease diagnosis of the brain, skin, liver, colon, kidney, bone, heart and other organs in the human body. The second-order nonlinear susceptibility of collagen has been explored at the macroscopic level and was explained as a volume-averaged molecular hyperpolarizability. However, details about the origin of optical second harmonic signals from collagen fibrils at the molecular level are still not clear. Such information is necessary for accurate interpolation of bio-information from nonlinear optical imaging techniques. The later has shown great potential in collagen based disease diagnosis methodologies. In this paper, we report our work using an atomic force microscope (AFM), near field (SNOM) and nonlinear laser scanning microscope (NLSM) to study the structure of collagen fibrils and other pro-collagen structures.